Relevamiento florístico en sistemas silvopastoril en el norte de Buenos Aires - Monsalvo, Maria Alexandra (2023)
The aim of this study is to understand the floristic composition of a disturbed natural pasture on a 93 ha of an agricultural establishment located in the north of the Buenos Aires Province. A silvopastoral system is implemented in the establishment with forest architecture of lines paired with 4 clones of Eucalyptus species. The floristic survey consisted of collecting each of the species present in the plots, supplemented by data on frequency of occurrence, associated species, and light/shadow incidence caused by the presence and spatial orientation of the Eucalyptus sp. crop. For sampling, the area was divided into two sectors according to the orientation of the crop, and each sector was further subdivided into four, considering the genotype of the Eucalyptus sp. clones. A total of 54 different species were recorded, belonging to 19 taxonomic families. It was determined that the predominant species belong to the POACEAE family, including species of forage interest, widely distributed in all the plots. There were identified 12 species with forage aptitude and 4 harmful species. This work constitutes a preliminary study to conduct seasonal surveys that will allow analyzing the succession of species with forage potential, species indicating environmental imbalances, and species harmful to livestock that grow spontaneously associated with each Eucalyptus clone. Moreover, this survey, along with the planned seasonal surveys, will enable the prediction of specific pasture management strategies for the system under study.